„Graikijos Vėjas“ by Algirdas Landsbergis: Features of the Narrative and Intertext of the Myth - Adomavičienė, Laimutė (Respectus Philologicus, 2017)
The article analyses novella “Graikijos Vėjas” (1956) of the exile prose writer, playwright, literary and theatre critic Algirdas Landsbergis (1924–2004) by applying the narratological analysis and the theory of transtextuality. The article is based on Gérard Genette’s classical narratology and the theory of transtextuality and Irina Melnikova’s theory of intermediality. It is an innovative approach since it has not been applied for the selected text so far. The analysis of novella’s narrative, space and time (order, duration, frequency) and narrative mode has shown that there exists the relation between time and space in the text. Temporal succession of events (one extended day) is described by providing the story of earlier events in a chronological order. The narrative is twofold: on the one hand, it consists of the fixed internal focalisation, on the other hand of zero focalisation. The analysis of transtextual relation between the own and others’ texts has revealed the significance of the context of the Greek culture. The writer uses the heritage of European mythology creatively: he transforms the classical myth of Theseus by ironizing the plot, reminding the love story of Theseus and making a parody of heroes’ former features (strength, bravery, noble ambitions and actions).